2014
DOI: 10.1089/ars.2013.5357
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase, NOX1, Mediates Vascular Injury in Ischemic Retinopathy

Abstract: Our findings suggest that strategies targeting NOX1 have the potential to be effective treatments for a range of ischemic retinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 57 publications
3
123
2
Order By: Relevance
“…Renal Nox4 gene expression was significantly reduced with both doses of GKT137831 and this may reflect reduced renal injury. Similar effects were recently reported in microglial and Müller cells exposed to hypoxia and treated with GKT137831 [32]. It is therefore possible that reduced expression and enzyme activity both contribute to the pharmacological effects of NOX inhibitors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Renal Nox4 gene expression was significantly reduced with both doses of GKT137831 and this may reflect reduced renal injury. Similar effects were recently reported in microglial and Müller cells exposed to hypoxia and treated with GKT137831 [32]. It is therefore possible that reduced expression and enzyme activity both contribute to the pharmacological effects of NOX inhibitors.…”
Section: Discussionsupporting
confidence: 84%
“…Taken together, the available data suggest that selective inhibition of NOX1 may be particularly effective to specifically prevent diabetes-induced vascular disease in conduit arteries and the retina [32]. NOX inhibitors with a broader selectivity profile, including NOX1, NOX4 and, possibly, NOX5 may represent more attractive therapeutic options in patients with associated kidney disease.…”
Section: Discussionmentioning
confidence: 96%
“…Knockout mice and inhibition studies strongly suggested NOX1 (green lines) as a therapeutic target in diabetic atherosclerosis (64), ischemic retinopathy (179), and-in interaction with NOX4-liver fibrosis (5,79,129). A role in melanoma progression and tumor angiogenesis (54) needs to be confirmed in NOX1 knockout mice, while a role of NOX1 in heart I/R injury (21) needs to be confirmed by pharmacologic inhibition of NOX1.…”
Section: Fig 7 Nox Enzymes As Validated Therapeutic Targetsmentioning
confidence: 99%
“…The first showed decreased lesion area and macrophage infiltration, two hallmarks of atherosclerosis, in NOX1/ApoE double KO mice after high fat diet feeding compared with ApoE KO mice (160); the second showed decreased atherosclerotic lesions and cellular surface adhesion factor CD44 in ApoE KO mice treated with GKT136901 (176). Very recently, NOX1 was also validated as a therapeutic target in ischemic retinopathy (179). Using a rodent model of retinopathy of prematurity, which is a major cause of blindness caused by damage to the retinal microvasculature, retinas of NOX1 KO mice showed reduced signs of retinopathy, such as neovascularization and avascular retina.…”
Section: Fig 7 Nox Enzymes As Validated Therapeutic Targetsmentioning
confidence: 99%
“…Utilising this model has led to significant insight into a role for oxidant stress in driving diabetic neovascularisation. For example, in NOX1, 2 and 4 knockout mice, the NOX1 isoform was shown to be the predominant isoform driving retinal neovascularisation 92. Of significance, NOX1 knockout mice showed reduced adherence of inflammatory leucocytes to the vasculature coupled with a lower abundance of the macrophage‐like cells of the retina, namely the microglial cells, suggesting an interplay between reduced oxidative stress and pro‐inflammatory mediators.…”
Section: Diabetic Retinopathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 99%